Plan de incentivos laborales en la Empresa Industria Metálicas Cotopaxi. - Analuca Arequipa, Héctor Davi (2023)
The performance of company workers "Industria Metálicas Cotopaxi", did not allow to get proposed work goals, due to lack organization to capture and retain talents and abilities of the collaborators to the assigned work. The main objective of this research is to design a work incentive plan to improve productivity and the work environment. The used methodology in the research was qualitative and quantitative, with a non experimental design, which led to reach it, through deductive method, and a field, descriptive, bibliographical and documentary research, in addition techniques and instruments which were used for the study were the questionnaire and field observation. The obtained results made it possible to show that workers aspire 100% labor incentives since they require by the work carried out efficiently and effectively be recognized. The origin of monetary and non-monetary work incentives based on an internal analysis is found and thus propose a healthy, optimal and enriching work environment for all workers, which should improve in the following years as produce the economic and commercial company development, without altering in any way the conditions already acquired by the company.